Extracellular matrix proteins as diagnostic markers of breast carcinoma. Issue 8 (9th March 2018) - Giussani, Marta; Landoni, Elena; Merlino, Giuseppe; Turdo, Federica; Veneroni, Silvia; Paolini, Biagio; Cappelletti, Vera; Miceli, Rosalba; Orlandi, Rosaria; Triulzi, Tiziana; Tagliabue, Elda
Abstract : Changes in amount and composition of extracellular matrix (ECM) are considered a hallmark of tumor development. We tested the hypothesis that abnormal production of ECM components leads to blood‐released ECM molecules representing tumor circulating biomarkers. Candidate genes were selected through class comparison in two publicly available datasets and confirmed in paired normal and tumor associated fibroblasts from breast carcinoma (BC) specimens. Production and release of ECM molecules were evaluated in normal human dermal fibroblasts (NHDFs) treated with conditioned media from three BC cell lines. Plasma samples from healthy donors and from patients with malignant or benign breast disease were tested by ELISA for the presence of collagen 11a1 (COL11A1), collagen oligomeric matrix protein (COMP), and collagen 10a1 (COL10A1). Selected ECM molecules were investigated by IHC in malignant and benign specimens. In silico analysis of gene expression profiles identified 11 ECM genes significantly up‐regulated in tumor versus normal tissue. Western blot analyses revealed increased levels of molecules encoded by three of these genes, COL11A1, COMP, and COL10A1, in cell lysates and supernatants of conditioned NHDFs. Class comparison and class prediction analyses of two independent series of human plasma samples identified the combination of COL11A1, COMP, and COL10A1 as potentially informative in discriminating BC patients from those with benign disease. The three molecules resulted expressed in the stroma of BC tissue samples. Our results indicate that circulating COL11A1, COMP, and COL10A1 may be useful in diagnostic assessment of suspicious breast nodules and ECM molecules could represent an avenue to biomarker identification. Abstract : We tested the hypothesis that abnormal production of extracellular matrix (ECM) components leads to blood‐released ECM molecules representing tumor circulating biomarkers. Levels of COL11A1, COMP, and COL10A1 molecules in human plasma samples resulted potentially informative in discriminating BC patients from those with benign disease. Circulating COL11A1, COMP, and COL10A1 may be useful in diagnostic assessment of suspicious breast nodules and ECM molecules could represent an avenue to biomarker identification.